A MODEL FOR H2O SOLUBILITY MECHANISMS IN ALBITE MELTS FROM INFRARED SPECTROSCOPY AND MOLECULAR ORBITAL CALCULATIONS - Sykes D.; Kubicki J.D. (My University, 1993)
Infrared spectra of H 2 O - and D 2 O - NaAlSi 3 O 8 (albite) glasses were measured and contain two major differences from the anhydrous glass spectra. The first is the presence of a number of bands above 3000 cm -1 arising from O-H stretching modes. The second change in hydrous glass spectra is the appearance of a shoulder at approximately 900 cm -1 . No frequency shift of the 900 cm -1 shoulder was detected with H-D substitution. We conclude, based on our infrared spectra and molecular orbital calculations as well as previous NMR ( et al., 1989) and Raman ( and , 1986a) spectra, that the 900 cm -1 band in the vibrational spectra of H 2 O-albite glass arises from an Al-(OH) stretching vibration in an Al Q 3 site. The model proposed in this paper is that below 30 mol% [H 2 O] tot , molecular water interacts with the network A1 3+ to produce Al-(OH) and a minor concentration of Si-(OH) bonds. Above 30 mol% [H 2 O] tot , the dominant species is molecular H 2 O and H + exchanges with Na + at the charge-balancing site to produce molecular NaOH or hydrated Na + ( H 2 O ) n , complexes in the melt.